IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILAMELALUI HASTA KARYA UNTUK PENDIDIKAN KARAKTER - Aquarius, Fergin (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2025)
This study examines the implementation of the Project-Based Learning for Strengthening the Pancasila Student Profile (P5) at SD Negeri 7 Batu Ampar, with a focus on reinforcing the character traits of critical thinking, creativity, and collaboration through the creation of handicrafts made from waste or repurposed materials. Employing a qualitative case study approach, data were collected through observation, interviews, and document analysis to explore the challenges in implementing a project under the theme of sustainable lifestyle. Students were grouped according to their learning phases to carry out contextual projects that align with their characteristics and the school environment. The project integrates character education with the dimensions of Pancasila by allowing students to produce diverse handicrafts based on their talents, interests, and prior abilities. The findings indicate that the co-curricular learning strategy facilitates the achievement of the intended goal of strengthening student character. This study offers guidance for teachers in implementing the P5 program in accordance with the guidelines of the Ministry of Education, Culture, Research, and Technology, and provides insights into addressing challenges in project-based learning within primary school settings.